2017
DOI: 10.1016/j.gore.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Vulvar condylomatosis after sex reassignment surgery in a male-to-female transsexual: Complete response to imiquimod cream

Abstract: BackgroundThe number of patients seeking sex reassignment surgery is increasing. Approximately 1:30,000 adult males and 1: 100,000 adult females seek this procedure. Neovaginal-related disorders after sex reassignment surgery are increasingly more common. Vulvar condylomatosis is the clinical manifestation of HPV 6- and 11 infection in biological women. The same HPV-subtypes are associated with anogenital warts and penile intraepithelial neoplasia in biological men. We aim to present a case of vulvar condyloma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Reported treatments ranged from patient-administered methods podophyllotoxin or imiquimod, to physicianoperated methods, including CO 2 laser ablation, electrovaporization, surgical excision, and total colpectomy. [11][12][13][14][15][16][17][18] To our knowledge, this is the first case report of neovaginal warts successfully treated with TCA.…”
Section: Discussionmentioning
confidence: 80%
“…Reported treatments ranged from patient-administered methods podophyllotoxin or imiquimod, to physicianoperated methods, including CO 2 laser ablation, electrovaporization, surgical excision, and total colpectomy. [11][12][13][14][15][16][17][18] To our knowledge, this is the first case report of neovaginal warts successfully treated with TCA.…”
Section: Discussionmentioning
confidence: 80%
“…98 studies reported outcomes on sexual activity and behaviour 11,18,19,29‐31,33‐38,41‐45,47,48,50‐53,58,63‐65,67‐74,76‐80,87,91‐94,98‐150 . Of the standardized questionnaires, the Sheffield Prolapse Questionnaire and BISF‐W included questions about frequency of sexual activity 34,106,151 .…”
Section: Resultsmentioning
confidence: 99%
“…112 Verruca vulgaris-producing HPV strands presented in two cases, in which both patients had greater than one cis man sexual partner and was treated with imiquimod cream. 120,126 Matsuki et al (2015) also treated the lesions with a CO 2 laser. 126 High-risk HPV (hrHPV) strains were randomly sampled in 54 patients, and 6 women (all sexually active) tested positive for various hrHPV strains.…”
Section: Detection Of Covid-19 In the Male Reproductive Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a consensus among health professionals that transsexual surgery and hormonal procedures have a positive impact on this dysphoria, although some people do not intend to undergo the surgical procedure to express their gender and identity role 3 . The number of people seeking SR surgery is gradually increasing 4 . There is a worldwide estimation that 1:30,000 adult trans women and 1:10,000 adult trans men seek the procedures annually.…”
Section: Introductionmentioning
confidence: 99%